Penyuluhan Kesehatan Tentang “Perilaku Hidup Bersih Dan Sehat (PHBS) Pada Remaja: Langkah Sederhana Lawan Diare” Di SMP IT Subulussalam Samarinda - Ilham; Nova Anggraeny Elistiawaty; Yusnita Safrina; Barolym Tri Pamungkas (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Diarrhea remains a significant public health problem in Indonesia. Data show a high prevalence among vulnerable groups, including adolescents who have busy daily activities, frequently consume food outside the home, and have low personal hygiene practices. This activity aimed to improve students’ knowledge of Clean and Healthy Living Behavior (PHBS) as an effective strategy for preventing diarrhea. The education was delivered through interactive lectures supported by leaflet media, and its effectiveness was measured using pre-test and post-test assessments. The health promotion titled “Clean and Healthy Living Behavior (PHBS) Among Adolescents: Simple Steps Against Diarrhea” at Subulussalam Integrated Islamic Junior High School showed an increase in participants’ knowledge from 79.6% to 88.2%.